Maintaining close contact from a distance: digital aikido training under COVID-19 conditions - reflections and lessons from an online martial arts course - Kantzara, V.; Loos, M. (Martial Arts Studies, 2019)
This work explores, reports, and reflects on the teaching and learning aspects of online courses in aikido, a peaceful martial art, under COVID-19 lockdown conditions in Greece. The essay is based on research and auto-ethnographic accounts of the digital courses the authors of this text have set up as teachers of aikido during the pandemic. There is little research on pedagogic and didactic issues of designing online courses in martial arts or on outcomes of digital learning. Thus, the present text aims to explicate the theoretical background drawn from different scientific disciplines in designing an online course in a martial art. This course attempted to meet the challenge of teaching online an art that `normally` is taught face to face, entailing physical practice in pairs. The essay explores and reflects also on the outcome of online learning under pandemic conditions. These are mostly social in nature, for the lessons and the contact strengthened the members in many ways. Thus, the ramifications of online teaching and learning are far reaching as they affect the participants and their families helping them to maintain a sense of wellbeing or normality under trying conditions. The social aspect of teaching a martial art online showcases its changing nature as well as its potential and possibilities for contributing to social cohesion, in the face of the grave dangers the current pandemic poses for humanity. It is an aspect of martial arts that could be taken into account when discussing their future in society.